Effect of supplementation with Escherichia coli phytase for broilers on performance, nutrient digestibility, minerals in the tibia and diet cost - Dessimoni, Gabriel Villela [UNESP]; Sakomura, Nilva Kazue [UNESP]; Donato, Daniella Carolina Zanardo [UNESP]; Goldflus, Fábio; Ferreira, Nayara Tavares [UNESP]; Dalólio, Felipe Santos (Universidade Estadual de Londrina, 2019)
Although phytase has been researched, new enzymes have been produced, leading to different animal responses. In this scenario, the present study proposes to evaluate the inclusion of a bacterial phytase produced by Escherichia coli in broiler diets based on corn and soybean meal, with or without nutrient reductions, on the performance, nutrient digestibility, phosphorus bioavailability, and bone minerals of those animals and on the economic viability of this practice. A total of 896 male broiler chickens were distributed into 32 experimental units, each housing 28 broilers. The experiment was set up as a completely randomized design with four treatments (Positive Control (PC)- diet meeting the nutritional requirements of the broiler chickens; Negative Control (NC) with reductions of 100kcal/kg of ME, 0.14% avP and 0.11% tCa; NC + phytase (500 FTU/kg); PC + phytase (500FTU/kg)) and 8 replicates. Phytase increased (p < 0.05) feed intake and body weight gain and improved feed conversion ratio in starter (1 to 21 days) and total (1 to 42 days) phases, respectively, compared with Negative Control diet without supplementation. The Negative Control + phytase diet also led to a feed intake similar to Positive Control in the starter and total phases. The inclusion of phytase without nutrient reductions improved (p < 0.05) feed conversion ratio in the starter phase, compared to Positive Control diet. There was an increase (p < 0.05) in the digestibility of dry matter, crude protein and phosphorus and in apparent digestible energy in the Negative Control + phytase diet compared to the Negative Control diet. Phytase supplementation increased (p < 0.05) the digestibility of crude protein, calcium and phosphorus, and apparent digestible energy compared to Positive Control diet. Ash, phosphorus, and calcium contents were higher in the Negative Control + phytase diet compared with those observed in the Negative Control diet without enzyme (p < 0.05). The Positive Control + phytase diet provided higher ash contents (p < 0.05), but calcium and phosphorus deposition was similar to those obtained with Positive Control diet. Phytase inclusion allows for a reduction in the diet cost per ton of produced feed. In conclusion, dietary supplementation with bacterial phytase produced from Escherichia coli for broiler chickens is recommended, as it provided increases in production performance, nutrient digestibility, and energy metabolizability and a reduction in the diet cost.
Keywords: Bioavailability; Calcium; Exogenous enzyme; Phosphorus; Poultry production